Thinking indigenous agency: contexts, actors and changing processes between guarani Indians (XVIIth. C.) - Perusset, Macarena (2015)
At the multiethnic and multicultural colonial Paraguay’s space, some people played a central role as intermediaries between different cultural traditions. Within this context, in the reducciones de indios emerged a new kind of actors who displayed a diversity of strategies in order to preserve indigenous welfare as self-profit. These were the guaraní leaders, a kind of cultural bridges as well as political and economic agents because of the daily practices they play in thecolonial society.